Baseline characterization of aquaculture systems and livelihoods in Nasarawa– Nigeria. Grow Out Farmers dataset - Lozano, Denise; Manyise, Timothy; Ghazali, Saadiah; Roslan, Shazleen (2023)
Baseline characterization of aquaculture systems and livelihoods in Nasarawa– Nigeria. Grow Out Farmers dataset. This study was conducted to understand how fish farming is practiced in this area.